UMKM Mothers Literacy Understands Household Accounting in Facing the New Normal Era (Study on UMKM Mothers in Pekanbaru City) - Eny Wahyuningsih; Muhammad Ariyon; Ellyan Sastraningsih (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Household accounting is not yet popular in Indonesia due to various factors. Among them are ignorance of its uses, such as providing peace because there is no financial deficit, self-control because following the budget that has been made, and satisfaction when the decisions are made right and the realization of long-term plans as revealed by several studies conducted by scholars in Indonesia. The participants of this community service are the housewives of Bakulan Kue. Because household accounting practices can be carried out by families who already have incomes that exceed the minimum standard of living. This is caused by low income in poor households, all income will be spent on consumption. The information that we provided turned out to be something that had not been practiced by the participants, especially in terms of recording. However, some of the participants have done budgeting in a simpler way by making allocations of daily and monthly expenditures in separate posts but without recording